2013
DOI: 10.1097/brs.0b013e3182a211c0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Swedish Version of the Scoliosis Research Society–22 (SRS-22r) Patient Questionnaire for Idiopathic Scoliosis

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 33 publications
0
14
1
1
Order By: Relevance
“…Cheung et al 23 preconsultation treatments, which may affect the internal consistency of that domain. Other authors 20,22,27,28 have reported high ceiling percentages in the pain domain of SRS-22, which was not observed in our study, although the patients had considerable level of pain.…”
Section: Discussioncontrasting
confidence: 76%
“…Cheung et al 23 preconsultation treatments, which may affect the internal consistency of that domain. Other authors 20,22,27,28 have reported high ceiling percentages in the pain domain of SRS-22, which was not observed in our study, although the patients had considerable level of pain.…”
Section: Discussioncontrasting
confidence: 76%
“…The disease-specific SRS-22r contains 22 questions covering five domains: function/activity, pain, self-perceived image, mental health, and satisfaction with treatment, scored from 1 (worst) to 5 (best) [17]. The 20 questions related to the first four domains were analyzed in this study and collated to make the SRS-22r subscore.…”
Section: Methodsmentioning
confidence: 99%
“…Questionnaires SRS-22r is a scoliosis specific instrument developed aiming to measure quality of life outcomes in scoliosis patients. It has been translated to Swedish and has been tested regarding reliability and validity [12]. The questionnaire comprises 22 questions distributed over five domains (function, pain, self-image, mental health and satisfaction) and each domain has five answers (one being the worst and five the best).…”
Section: Individualsmentioning
confidence: 99%